Activity Report, Section 1c / AO (Abwehr Officer), Headquarters, 20th Mountain Army, for the time period July 1 to December 31, 1943. (1943)
Activity report for the German 20th Mountain Army. Taken from microfilm Records of the German Field Command, Armies, National Archives Series T-315, 210th Infantry Division, folder 45787/2, 1c frame 000577. Translated by Major James F. Gebhardt, USA (retired).